Tafsir Dalam Ulumul Quran di Era Modern Kontemporer - Jannah, Miftahul (Ulumul Syari, 2017)
The understanding and interpretation activities of the Quran will never be completed. The dialectic also experiences ups and downs along with the openness, skill and ability of an interpreter. Each generation is required to be able to interact actively with the Quran through reading, interpretation and so on to refresh the previous review that may not have been applied. Thus, the emergence of new interpretations and methods in the present era is also inevitable and is a necessity in each generation to be able to bring it up. Al-Quran seen from various aspects is very interesting to be studied further in this modern-contemporary era, considering he not only became the consumption of Muslim society alone, the Quran also received a high response from non-Muslim circles. Many of the Western scholars respond to the presence of the Quran. Some of them initially suspected and rejected the study of the Quran, but in subsequent developments found many western scholars are very objective in the area of ââstudy of the Quran. Given this non-Muslim interaction with the Quran it also provides some impact for some Muslim scholars to then try to open up to learn the methodology used by non-Muslims both when interacting with the Quran and the methods they use When interacting with other texts. This arrangement ultimately gives an enormous impact and is very coloring in the development of interpretation among Muslims.